Pravljice kot didaktično sredstvo pri pouku slovenščine kot drugega/tujega jezika - Petrovčič, Teja (Sodobna pedagogika, 2025)
Applying folk tales in foreign language teaching promotes the linguistic, emotional, and cognitive development of children and adolescents while providing significant insights into a nation‘s culture, customs, and language. The theoretical part presents the position of Slovene as a second/foreign language and Russian as a foreign language within the Slovenian educational system and describes the role of artistic texts, particularly folk tales, as a literary genre. We also highlighted the differences in the presence of folk tales in the curricula for Slovene and Russian and explained the origins of these differences. To further illuminate the benefits of folk tales and assist educators, the central part of the article provided practical examples of using folk tales in teaching Slovene as a second/foreign language and Russian as a foreign language. We emphasized that Slovenian and Russian folk tales, as didactic tools, possess numerous linguistic and lexical features that contribute to developing language skills, thereby supporting students in learning Slovene as a second/foreign language and Russian as a foreign language.
Keywords: didactics; didaktika; ruske ljudske pravljice; Russian folk tale; Slovenian as a second/foregin language; Slovenian folk tale; slovenske ljudske pravljice; slovenščina kot drugi/tuji jezik